Impact of Technological Changes on Job Performance of Teachers in Higher Education Institutions: A study with reference to quality accredited colleges in Province 2, Nepal (Research Journal on Multi-disciplinary Issues, 2021)
This article assessed the impact of technological changes on job performance of teachers with evidence from quality accredited higher education institutions in province 2, Nepal. The study has been conducted using a descriptive survey research design. The population consists of 105 academic staffs of two quality accredited higher education institutions of province 2. Convenience sampling techniques were employed to select the sample size of 57academic staffs from the population. Regression analysis was used to analyze the data that was collected using a five-point Likert‘s scale structured questionnaire. The results showed that technology has influenced job performance of teachers since it simplifies the work to be done. Technology greatly escalates the productivity of employees along with time saving. Use of ICT and the internet can assist teachers to instruct efficiently and students learn more effectively. Thus, to enhance and strengthen the quality of our education, it is the need of the hour to digitize the teaching and learning methodologies. But technological changes adoption in quality accredited higher educational institutions in province 2 is low.